Analisis Kualitas Produk dan Harga dalam Mempengaruhi Keputusan Pembelian Sepeda Motor Yamaha Nmax di Kota Gorontalo - Fikriawan; Umar, Zainal Abidin; Asnawi, Melan Angriani (Ikatan Da'i Indonesia, 2024)
This study aims to analyze the influence of product quality and price on the purchase decision of Yamaha Nmax motorcycles in Gorontalo City. Data was collected through a questionnaire that had been tested for validity and reliability. The study's population consists of 1,836 consumers who purchased Yamaha Nmax motorcycles at PT. Hasjrat Abadi Yamaha 3S Ahmad Yani Gorontalo from 2021 to 2023. A sample of 95 respondents was selected using non-probability sampling with the accidental sampling method. Data analysis was conducted using multiple linear regression. The results show that both product quality and price have a positive and significant partial influence on purchase decisions. Simultaneously, these two variables also have a significant influence. The R Square value of 0.656 indicates that 65.6% of the purchase decision is influenced by product quality and price, while the remaining 34.4% is influenced by other variables not examined in this study.